Entrepreneurship and creative professions: A micro-level analysis - Michael Fritsch; Alina Sorgner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
It has widely been recognized that creativity plays an immense role not only for arts, sciences, and technology, but also for entrepreneurship, innovation, and thus, economic growth. We analyze the level and the determinants of self-employment in creative professions at the level of individuals. The analysis is based on the representative micro data of the German Socio-Economic Panel (SOEP). The findings suggest that people in creative professions appear more likely to be self-employed and that a high regional share of people in the creative class increases an individual's likelihood of being an entrepreneur. Investigating the determinants of entrepreneurship within the creative class as compared to non-creative professions reveals only some few differences.
Keywords: L26; Z1; D03; 330; entrepreneurship; new business formation; creativity; creative class